Transformative Digital Innovations : Redefining Education in the Post-Pandemic Era (Universitas Kristen Indonesia Toraja, 2023)
The COVID-19 pandemic accelerated the adoption of digital tools in education. This paper explores transformative innovations in educational technology, focusing on adaptive learning platforms, gamification, and AI-driven assessments. Case studies from developed and developing nations are presented to highlight successful implementations and challenges. The findings demonstrate how these innovations contribute to inclusive, flexible, and effective learning environments.